Penerapan Prinsip Keseimbangan Antara Kepentingan Umum dan Swasta dalam Peraturan Perpajakan - Awaliyah Matondang, Khairani; Siagian, Hernita; Novita Br Kaban; Hutagalung, Marshanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The government in Indonesia itself carries out its duties and objectives within a government agency, written in article 1 paragraph 2 of the 1945 constitution. In 1962 Harberger stated that a tax burden theory was final by imposing a general consideration, which would be used in international trade. This research uses a qualitative method, namely a research method used to explain an event or social activity. This research aims to understand an event that will be studied in a comprehensive way. A country's income is obtained from its people, it can be seen from the method of tax revenue or some of it comes from the natural wealth of a particular country. Tax has the meaning of handing over property/wealth from a person or organization to a state agency or government of a country. An object of tax collection or receipt is an object that is almost the same as that object. A principle of tax revenue is basically a guideline for aligning government tasks.